Analisis Strategi Diskon Harga Dalam Meningkatkan Penjualan Sepeda Motor Merk Honda di PT Kencana Mulia Abadi Kota Gunungsitoli - Diana Kartika Sari Telaumbanua; Serniati Zebua; Yupiter Mendrofa; Nov Elhan Gea (Jurnal Publikasi Manajemen Informatika, 2024)
The main problems identified at PT. Kencana Mulia Abadi is the lack of variation in discount strategies. The discounts offered tend to be monotonous and not adapted to various market segments and only for certain types of motorbikes, not comprehensively for all types of motorbikes marketed. This research uses a descriptive approach with a qualitative research type where data collection techniques are obtained through interviews, observation and documentation. The data analysis technique used is the Milles and Huberman data analysis technique. The research results show that (1) Implementation of price discount strategies at PT. Kencana Mulia Abadi is considered to have significantly increased sales of Honda brand motorbikes, especially during certain periods such as special events or new product launches. Price discounts are effective in attracting consumers and speeding up stock turnover, helping manage excess stock and minimizing the risk of unsold products, and (2) Price discount strategies also contribute to increasing customer loyalty and competitiveness in the market. PT. Kencana Mulia Abadi is advised to implement a discount strategy that is planned and not too frequent, such as at annual events or new product launches, to avoid reducing the perception of product value. In addition, companies can increase customer loyalty by complementing discount strategies with attractive loyalty programs, such as reward points or exclusive vouchers, which can strengthen relationships with customers and encourage repeat purchases.